Meyer and Peng’s 2005 article as a foundation for an expanded and refined international business research agenda: Context, organizations, and theories - Kostova, Tatiana; Hult, G Tomas M (Journal of International Business Studies, 2016)
In this commentary we provide an assessment of the JIBS Decade Award-winning article by Meyer and Peng and its impact on the field of international business (IB). We highlight Meyer and Peng’s focus on a relevant and important phenomenon – the emergence of transition economies in Central and Eastern Europe (CEE) as a new class of markets. We address the CEE focus within the context of Meyer and Peng’s insightful organizing framework built on three organizational archetypes (foreign entrants, local incumbents, and new start-ups) and the applications of four theories in CEE research (transaction cost economics, agency theory, resource-based view, and institutional theory). Importantly, we suggest that the Meyer and Peng article can serve as a foundation for further expansion and refinement of IB research in non-Western contexts, including transition economies and the increasingly important emerging markets. To advance the literature, we also propose a set of ideas of how to push this research forward by expanding Meyer and Peng’s analysis of contexts, organizational forms, and theoretical perspectives. Regarding context, we discuss the risks of overgeneralization and aggregation and the need to follow a more precise categorization of national economies based on central theoretical characteristics. Regarding organization type, we expand the original set by focusing on state-owned or state-controlled enterprises and family firms. Similarly, we propose a more comprehensive and in-depth treatment of theories employed in research on transition economies and emerging markets to better explore the developments in these theoretical perspectives and utilize the unique framework of such contexts.